2018
DOI: 10.1038/s41467-018-05254-w
|View full text |Cite
|
Sign up to set email alerts
|

An autophagy assay reveals the ESCRT-III component CHMP2A as a regulator of phagophore closure

Abstract: The mechanism of phagophore closure remains unclear due to technical limitations in distinguishing unclosed and closed autophagosomal membranes. Here, we report the HaloTag-LC3 autophagosome completion assay that specifically detects phagophores, nascent autophagosomes, and mature autophagic structures. Using this assay, we identify the endosomal sorting complexes required for transport (ESCRT)-III component CHMP2A as a critical regulator of phagophore closure. During autophagy, CHMP2A translocates to the phag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
231
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 291 publications
(253 citation statements)
references
References 46 publications
10
231
0
Order By: Relevance
“…While the ESCRT membrane scission machinery was originally discovered for its role in ubiquitinated cargo sorting in the multivesicular body (MVB) pathway (Katzmann et al, 2001), recent studies have revealed its involvement in a number of other cellular processes, including virus budding, cytokinesis, microvesicle generation, plasma membrane wound repair, nuclear envelope reformation, nuclear pore complex quality control, and endolysosomal repair (Hurley, 2015; Christ et al, 2017; Skowyra et al, 2018). Most recently, we have used the HT-LC3 assay and demonstrated the requirement of the ESCRT-III component charged MVB protein 2A (CHMP2A) and VPS4 activation in phagophore closure (Takahashi et al, 2018). In this study, we have combined a genome-wide CRISPR library screen with the HT-LC3 assay and identified the ESCRT-I component vacuolar protein sorting-associated protein 37A (VPS37A) as a novel phagophore closure regulator.…”
Section: Introductionmentioning
confidence: 99%
“…While the ESCRT membrane scission machinery was originally discovered for its role in ubiquitinated cargo sorting in the multivesicular body (MVB) pathway (Katzmann et al, 2001), recent studies have revealed its involvement in a number of other cellular processes, including virus budding, cytokinesis, microvesicle generation, plasma membrane wound repair, nuclear envelope reformation, nuclear pore complex quality control, and endolysosomal repair (Hurley, 2015; Christ et al, 2017; Skowyra et al, 2018). Most recently, we have used the HT-LC3 assay and demonstrated the requirement of the ESCRT-III component charged MVB protein 2A (CHMP2A) and VPS4 activation in phagophore closure (Takahashi et al, 2018). In this study, we have combined a genome-wide CRISPR library screen with the HT-LC3 assay and identified the ESCRT-I component vacuolar protein sorting-associated protein 37A (VPS37A) as a novel phagophore closure regulator.…”
Section: Introductionmentioning
confidence: 99%
“…S1E). Finally, we tested whether autophagosome closure or autophagosome-lysosome fusion were required for TRIM5signaling by knocking down the ESCRT component CMHP2A (35), and the autophagosomeassociated (t)-SNARE SNAP29, and the lysosomal (v)-SNARE VAMP8, and found that these proteins were also essential for TRIM5-based signaling ( Fig. 2A,B; S1F).…”
Section: Resultsmentioning
confidence: 99%
“…6D; 1-0-10 ). During autophagy, CHMP2A translocates to the phagophore to regulate separation of the inner and outer autophagosomal membranes to form double-membrane autophagosomes [171]. CHMP2B is a member of the ESCRT-III complex required for efficient autophagy and has reduced expression in melanoma [172,173], raising the hypothesis that gemcitabine could have efficacy in that context.…”
Section: Resultsmentioning
confidence: 99%